Development method of students’ reading abilities through the study of literary reading - Meruyert Alibayeva, Zhanar Seisenbayeva, Saule Nurgali,; Shadiyeva, Nurgul; Yermekbayev, Muhtar (Opción, 2019)
The study aims to investigate the development method of students’ reading abilities through the study of literary reading via comparative qualitative research methods. As a result, rural and urban schools participating in the experiment are able to develop the reading abilities of high school students on a regular basis, using creative tasks taking into account the age characteristics of students, the volume of literary knowledge provided to them. In conclusion, one of the most important tasks of literary education in school is to develop students’ literacy skills in teaching epic poetry.